Wolbachia‐induced transcription factor GATA4 suppresses ovary‐specific genes blastoderm‐specific protein 25D and imaginal disc growth factor. Issue 3 (16th January 2018) - Osei‐Amo, S.; Hussein, M.; Asad, S.; Hugo, L.; Asgari, S.
Abstract: The endosymbiotic bacterium Wolbachia infects a wide array of insect hosts and has been implicated in a range of biological modifications as a consequence of its infection. Previously, it was shown that the transcription factor GATA4 was significantly induced in Wolbachia w MelPop‐CLA strain infected Aedes aegypti whole mosquitoes and cells. Here, we provide evidence that this induction also occurs in mosquito ovaries where the ovary‐specific genes blastoderm‐specific protein 25D ( Bsg25D ) and imaginal disc growth factor ( Disc ) are suppressed by Wolbachia . We further demonstrate that transcriptional depletion of GATA4 results in upregulation of both genes and conversely its overexpression leads to downregulation of the genes, suggesting that Wolbachia‐ induced GATA4 plays a suppressive regulatory role with regards to Bsg25D and Disc expression in mosquito ovaries. When the Disc gene was silenced in mosquitoes, we did not observe any difference in the number of mature ovarian follicles developed between treatment groups. However, we did find a significant delay in the hatching of eggs that had been laid by Disc knockdown mosquitoes.